ANALISIS PENDAPATAN PAJAK RESTORAN (STUDI KASUS KAFE) TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA BANJARMASIN - Muhammad Ilham Mubarak; Chairul Sa’roni (Universitas Lambung Mangkurat, 2021)
This final project research aims to determine the contribution, effectiveness and potential of restaurant tax revenue, especially from the cafeteria sector and its effect on local taxes and PAD Banjarmasin. The results of this final project are expected to be a consideration for the Banjarmasin City Financial Agency Office in utilizing the potential of taxes as a source of regional income in the future.